Locker Security System Design Based On Internet of Things (IoT) Android Interface - Winarno Fadjar Bastari; Muhammad Andri Eko Prasetyo; Indri Suryawati (BEST, 2021)
Technological sophistication is growing in various ways, for example in the security system of an object. Basically, the security system of an object is done manually which is less practical than today's technological systems. One application of the security system is for locker safety. Therefore, to overcome the security system in the locker, the solution is to create a security system that uses ESP32-CAM as an Internet of Things (IoT) android-based microcontroller for the android interface for the security system in the locker and when someone forcibly opens the ESP32-CAM module it will take a photo. the person to notify the user about the current state of the locker via the telegram application on android.